MicroRNA Dysregulation in Epilepsy: From Pathogenetic Involvement to Diagnostic Biomarker and Therapeutic Agent Development - Wang, Jialu; Zhao, Jiuhan (Frontiers in Molecular Neuroscience, 2021)
Epilepsy is the result of a group of transient abnormalities in brain function caused by an abnormal, highly synchronized discharge of brain neurons. MicroRNA (miRNA) is a class of endogenous non-coding single-stranded RNA molecules that participate in a series of important biological processes. Recent studies demonstrated that miRNAs are involved in a variety of central nervous system diseases, including epilepsy. Although the exact mechanism underlying the role of miRNAs in epilepsy pathogenesis is still unclear, these miRNAs may be involved in the inflammatory response in the nervous system, neuronal necrosis and apoptosis, dendritic growth, synaptic remodeling, glial cell proliferation, epilepsy network formation, impairment of neurotransmitter and receptor function, and other processes. Here, we discuss miRNA metabolism and the roles of miRNA in epilepsy pathogenesis and evaluate miRNA as a potential new biomarker for the diagnosis of epilepsy, which enhances our understanding of disease processes.